2016
DOI: 10.1097/bcr.0000000000000220
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Accumulation in the Small Intestine Contributes to Local Tissue Destruction Following Combined Radiation and Burn Injury

Abstract: Objective The threat of nuclear disaster makes combined radiation and thermal burn injury (CRI) a relevant topic when discussing modern trauma, as burn injuries are likely to occur with detonation of a conventional nuclear weapon. Previous studies in a murine model have shown that there is a breakdown of the gut epithelium and subsequent bacterial translocation into mesenteric lymph nodes after CRI. This study examines the early innate immune response of the small intestine following CRI. Methods Using a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…The extent of tissue damage caused by radiation has been reported previously (23, 24), but the effects of combined radiation and severe peripheral crush injury remain unclear. Histologic evaluation of the small intestine showed that initial damage to the gut at day 3 worsened at day 7 after TBX implantation (Fig.…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…The extent of tissue damage caused by radiation has been reported previously (23, 24), but the effects of combined radiation and severe peripheral crush injury remain unclear. Histologic evaluation of the small intestine showed that initial damage to the gut at day 3 worsened at day 7 after TBX implantation (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…In the model of combined burn (15% total-body surface) and TBI, combined injuries significantly increased lethality (911, 24). In an animal model of combined incisional wound inflicted 1 h prior to 9.6 Gy TBI, Kiang et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations